Faktorer associerade med hur lång tid katter spenderar på djurhem : en anpassad miljö kan leda till snabbare adoption - Sandberg, Katarina (SLU/Dept. of Animal Environment and Health (until 231231), 2017)
Every year, thousands of cats are relinquished to animal shelters in Sweden and around the world. To house these solitary animals in confined environments, and in close proximity to their conspecifics, is something that can lead to issues regarding their welfare. In this study cats housed singly or in pairs were observed to investigate whether the behavioural protocol ”Cat Behaviour and Wellbeing protocol” (Cat-Be-Well) could predict how long time a cat spent at the animal shelter before adoption and whether the characteristics of a cat had any influence on this time. An accompanying literary study was conducted to determine how a cat’s environment could be adapted so that the cat would display behaviours previously associated with adoption. The results of this study indicate that the behavioural protocol used can, indeed, predict time spent at the shelter. This means that the shelter personnel will potentially be able to use the protocol to identify which cats are at risk of spending a longer time at the shelter, and thus may need extra resources. The study also shows that a cat’s characteristics might influence the adopter’s choice of cat, though it seems like the behaviour of the cat is more important. According to this study a cat that is not stressed has a better chance at getting adopted than a cat that is stressed. This means that a cat’s environment should be adapted in a manner that allows the cat to live a life that is as stress-free as possible. This can be done by modifying the cat’s surroundings, not only after its natural behaviours by adding shelves, hides, and hunting opportunities, but also to its senses. As cats have a better sense of smell, better hearing and better eyesight than humans, stimuli adapted to humans can be perceived as aversive by cats. By considering everything from the lightbulbs to the cleaning solutions from a cat’s point of view, a lot of the aversive stimuli can be removed, which leads to more comfortable cats with a greater chance for adoption.